Manajemen Resiko Proyek Untuk Mencegah Terjadinya Pemutusan Kontrak Kerja Pada Proyek Abrasi Pantai Desa Biluhu Tengah - Rahman Abdul Djau (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
This reseach was conducted on the project construction of abrasion beach located in the village of Biluhu middle district biluhu. Data collection was performed by questionnaires. The results of the survey questionnaire collected the 30 responpondents, then the data is analyzed with statistical analysis. Based on the test reliability coefficient obtained Cronbach Alpha of 0,637, thus it can be concluded that this variable realibe. The results of this study conducted with the test statistics and performed the ranking over the factors that cause the termination of the employment contract.based on the ranking, there are 8 (eight) factorsthat cause the occurrence of the termination of the emplyment contract that the employment relationship that is not harmonious with the owner, the method of implementation, shortage of labor, delays the star of the work, materials delivered are not in accordance, the working relationship that is not harmonious with the supervision consultant, the shortage of funds in the implementation of and mistake to interpret the image.